FAKTOR-FAKTOR ADOPSI INOVASI PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI DESA HALUBAU DAN DESA JIMAMUN KABUPATEN BALANGAN - , Dian Nugrahini, Ir. Leksono Probo Subanu, MURP,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pamsimas program as the continuation of WSLIC program is a government program in drinking water and sanitation community base.This program purpose is to achieve MDGâs target to reduce to half amount of the community without safe drinking water access and sanitation in 2015. The secondary data shows the enhancement access of clean water and sanitation facility which should be followed by the hygienic and healthy life behavior of the community (Pamsimas outcome). It is assumed that innovation adoption theory will able to explain change behavior of the Pamsimas village community. The purpose of this research is to identify and analyze the factors to explain the innovation adoption process of the hygienic and healthy at Halubau and Jimamun Village Balangan Regency. The approach of this research is quantitative deductive with survey method. The researchâs characteristic is correlation descriptive/ associative and comparative which carried out with non-experimental research approach. The analysis technique in use is relation test (Chi square) and differential test (U Man Whitney). The result shows the innovation adoption level PHBS practice is very low because collective decision character, forced nature innovation, creates a discontinuity. Inter free variable relation test shows the relation among agent of change role and knowledge, interaction/ relation mobility and personâs knowledge and motivation, relation perception and behaviore, relation knowledge and behavior to the PHBS innovation. The result of free and related variable relation hypothesis test is there are no relation between behavior adoption and social economic characteristic variable (age, education, job, salary, and interaction), knowledge, motivation, behavior, innovation perception and the agent of change role. There is a different innovation adotion in Hulubau village and Jimamun village. PHBS adoption rate of the Halubau Villageâs community is higher than the Jimamun Village. Project output could be considered success